Seminário Episcopal de São Paulo e o paradigma conservador do século XIX - Martins, Patrícia Carla de Melo (2006)
Ubiquity in Brazilian Catholicism turns it into a rich object of analysis in order to understand the effectual culture at different regions of the country. It is a religion that has extended its characteristics over different features of Brazilian regionalism and, at the same time, follows the historical, cultural and political transitions of the country. The research focused upon the conjunctural analysis of Catholicism in the state of São Paulo favors the place of elaboration of elementary meanings for the catholic structural organization in face of a contemporary modernity, without which it would not be possible to reach its superstructure that has come along with processes of complexification of global societies. The Episcopal Seminary of São Paulo, founded in 1856, is evaluated in this research as a structuring element of the Brazilian Catholicism in the second half of the 19th century. Based on the premises of Cultural History, built on the basis of Anthropology and Sociology of culture, religion is a place of language production, a means of communication which, as such, produces a structure of knowledge. In order to reach certification of this classification of Catholicism which legitimates practices and social-cultural representations in the territory of São Paulo, we analyzed documents produced and used by the Episcopal Seminary of São Paulo, commemorative polyantheas; meeting minutes; statutes and intern regulations; accountancy books, personal correspondences, among others which constituted the structuring basis of the educational system that was applied there. The Seminary of São Paulo was founded to serve the interests, not only of the Roman Catholic hierarchy, which turned the Catholicism into an universal religion, but also to attend the interests of the Brazilian Crown regarding the support of conservative ideals which were being threatened by the political liberalism. The education divulged at the Seminary contributed to the formation of a group of conservative intellectuals, who defended a hierarchic political order, a theological philosophy permeated by medieval metaphysics references, and a religious doctrine that legitimated the permanence of the clergymen oriented by the Pope of Rome as the holders of true Christian tradition